2005
DOI: 10.1128/jb.187.19.6816-6823.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Phenotypic Convergence Mediated by GGDEF-Domain-Containing Proteins

Abstract: GGDEF domain-containing proteins have been implicated in bacterial signal transduction and synthesis of the second messenger molecule cyclic-di-GMP. A number of GGDEF proteins are involved in controlling the formation of extracellular matrices. AdrA (Salmonella enterica serovar Typhimurium) and HmsT (Yersinia pestis) contain GGDEF domains and are required for extracellular cellulose production and biofilm formation, respectively. Here we show that hmsT is able to restore cellulose synthesis to a Salmonella ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 47 publications
1
62
1
2
Order By: Relevance
“…HmsT and HmsP are hypothesized to control Hms-dependent ECM biosynthesis via their opposing c-di-GMP forming and degrading activities. In keeping with this regulatory scheme, copy number of hmsT is directly related to c-di-GMP levels and biofilm thickness in Y. pestis; conversely, deletion of hmsT or disruption of its GGDEFencoding region result in poor biofilm formation Simm et al 2005). As also predicted by the model, elimination of HmsP or its EAL domain result in thicker biofilm ).…”
Section: Regulation Of Hms-dependent Biofilm Formationmentioning
confidence: 62%
See 1 more Smart Citation
“…HmsT and HmsP are hypothesized to control Hms-dependent ECM biosynthesis via their opposing c-di-GMP forming and degrading activities. In keeping with this regulatory scheme, copy number of hmsT is directly related to c-di-GMP levels and biofilm thickness in Y. pestis; conversely, deletion of hmsT or disruption of its GGDEFencoding region result in poor biofilm formation Simm et al 2005). As also predicted by the model, elimination of HmsP or its EAL domain result in thicker biofilm ).…”
Section: Regulation Of Hms-dependent Biofilm Formationmentioning
confidence: 62%
“…hmsT and hmsP, two recently identified chromosomal genes that are unlinked to the hmsHFRS locus and to each other, encode a GGDEF-domain protein with c-di-GMP synthesizing diguanylate cyclase activity and an EAL-domain protein with phosphodiesterase activity, respectively (Bobrov et al 2005;Hare and McDonough 1999;Jones et al 1999;Simm et al 2005). HmsT and HmsP are hypothesized to control Hms-dependent ECM biosynthesis via their opposing c-di-GMP forming and degrading activities.…”
Section: Regulation Of Hms-dependent Biofilm Formationmentioning
confidence: 99%
“…S5). Both genes were selected because their products have been demonstrated to possess DGC activity at 28°C (12,32). Results indicated that ⌬XIIϩP 4551 adrA and ⌬XIIϩP 4551 hmsT exclusively recovered the capacity to synthesize cellulose in a process strictly dependent on DGC activity, because ⌬XIIϩP 4551 adrA and ⌬XIIϩP 4551 hmsT strains containing a degenerate GGGSF motif lost their capacity to activate cellulose synthesis.…”
Section: Consequences Of Removing All Ggdef-domain Proteins In a Singlementioning
confidence: 99%
“…HmsP, a negative regulator of biofilm formation, is an EAL phosphodiesterase and likely degrades c-di-GMP. Like other glycosyltransferases involved in EPS or cellulose productions, the enzymic activity of HmsR may depend upon c-di-GMP (Bobrov et al, 2005;Hare & McDonough, 1999;Jones et al, 1999;Kirillina et al, 2004;Perry et al, 2004;Simm et al, 2005).…”
Section: Introductionmentioning
confidence: 99%